Factors inducing productivity: a qualitative and quantitative view of Portuguese companies. (30th September 2022) - Correia, Daniel; Reis, Pedro; Pinto, Pedro
This research aims to recognise the impact of communication, training, joint commitment, leadership practices, and corporate bonuses as productivity predictors. For this purpose, a questionnaire survey was used to obtain a longitudinal case study involving 147 semi-structured interviews with employees and managers engaging in different roles. Then, factor analysis and multivariate data analysis were used to identify the inductors of labour productivity along the hierarchical chain. The results indicate that regardless of the hierarchical level in which the responsibilities are performed, it was possible to identify labour productivity inductors. This work's originality remains on a holistic approach of employee recognition, motivation, engagement, compensation, communication, training, leadership style, and company type as global potential determinants for labour productivity for SMEs. The main limitations stem from the statistical technique used (cross-section analysis) and the restricted geographic scope. This study provides management tools that help promote worker productivity and management efficiency regardless of their hierarchical level.